Pete the Kitty goes to the doctor - Dean, Kim, 1969-; Dean, James, 1957- (Pete the kitty., 2019)
When Pete the Kitty has a stomach ache, his dad decides that it is time to go to the doctor, but Pete is a little bit nervous about his first visit to the doctor.